Architecture of eukaryotic mRNA 3'-end processing machinery - Casañal, A; Kumar, A; Hill, C; Easter, A; Emsley, P; Degliesposti, G; Gordiyenko, Y; Santhanam, B; Wolf, J; Wiederhold, K; Dornan, G; Skehel, M; et al. (American Association for the Advancement of Science, 2017)
Newly transcribed eukaryotic pre-mRNAs are processed at their 3'-ends by the ~1 MDa multiprotein cleavage and polyadenylation factor (CPF). CPF cleaves pre-mRNAs, adds a poly(A) tail and triggers transcription termination but it is unclear how its different enzymes are coordinated and assembled. Here, we show that the nuclease, polymerase and phosphatase activities of yeast CPF are organized into three modules. Using cryo-EM, we determine a 3.5 Å resolution structure of the ~200 kDa polymerase module. This reveals four beta propellers in an assembly strikingly similar to other protein complexes that bind nucleic acid. Combined with in vitro reconstitution experiments, our data show that the polymerase module brings together factors required for specific and efficient polyadenylation, to help coordinate mRNA 3'-end processing.